Variation factors in the population structure and fibre production in vicuñas of the Cusco Region, Peru - Pacheco C., Joel Iván (2020)
The vicuña is an emblematic species of fauna conservation in Peru. The vicuña population recovered after several years of timely measures for their conservation, moving to appendix II of CITES. Currently there are vicuñas that are kept free (silvestry) and populations kept enclosed in permanent fences (captivity). During 2018, 58 programmed captures (known as Chacus) were done in the Cusco Region, capturing 6777 animals, corresponding to 3229 and 3548 heads for silvestry and captivity, respectively. The age distribution in the case of juveniles was higher in silvestry (18.08%) with respect to the captivity system (7.2%), which would be evidence of the existence of higher mortality in this population. The 2012 national census indicated a higher proportion of female vicuñas in the general population of the Cusco Region; however, in this work similar populations were found by sex in both rearing systems. The proportion of vicuñas sheared with respect to those captured was 52.95 and 30.21% for silvestry and captivity, respectively, while fibre production was 172.4 and 156.7 g per animal on average for silvestry and captivity, respectively. These results lead to the possibility of rethinking the use of permanent fences in the breeding of vicuñas in captivity to produce fibre, considering the lower productive levels obtained in this management system.